Aplikasi Game Puzzle Pengenalan Perangkat Komputer Berbasis Android - Burhan Arifin; Zulfikar -; Agus Sifaunajah (SAINTEKBU, 2018)
Mobile device technology is growing rapidly, especially with the emergence of smartphones with Android operating system. Users, in this case, can download a variety of basic applications available easily in the google play store. But most are available in the form of less educational games. Even often the negative impact on users, especially for children who still can not distinguish positive and negative. Thus the researchers create a puzzle game application that can provide entertainment and education to users, especially children. The puzzle game application introduces this selected computer device built using Construct 2 game engine converted with Phonegap into Apk files. Application of this application by installing puzzle game application on a smartphone with operating system specification android version 4.4.2 KitKat. Keywords: Educational Game, Computer Device, Construct 2